Gender Transition and Job In/Security: Trans* Un/der/employment Experiences and Labour Anxieties in Post-Fordist Society - Irving, Dan (Atlantis)

(untitled) (Mount Saint Vincent University, 2017)
Undergoing gender transition is a risky endeavor in these violent times. Transitioning signifies the affirmative of self and new beginnings; however, the extent to which transition can mark the start of a new life is framed by one’s social location vis-a-vis material power relations. Un(der)employment allows a glimpse into why particular bodies are rendered worthless. This article draws from my larger qualitative study addressing trans* un(der)employment in Ontario, British Columbia, and Washington State.